1984
DOI: 10.1007/bf03348432
|View full text |Cite
|
Sign up to set email alerts
|

Apparent free Cortisol concentrations in patients with anorexia nervosa at different stages of the disease

Abstract: We have measured the total cortisol concentration (TC) and the apparent free cortisol concentration (AFCC) in plasma samples of 17 patients with anorexia nervosa (AN) at different stages of the disease, in basal conditions and after suppression test. We measured free cortisol values directly by a RIA method in dialyzed plasma samples after an equilibrium dialysis system. We have found significantly elevated TC and AFCC values in basal conditions and after suppression test only in the group of patients in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In addition, given that AN is associated with undernutrition and hypogonadism, one would expect low, rather than high, CBG levels. The binding capacity of CBG for cortisol does not differ in adults with AN compared with controls (12), and elevations have been reported not only in total, but also in free plasma cortisol in adult AN women (20,37). To determine whether an acquired partial glucocorticoid resistance is the cause of hypercortisolemia in AN, investigators have examined expression of glucocorticoid receptors in adults with this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, given that AN is associated with undernutrition and hypogonadism, one would expect low, rather than high, CBG levels. The binding capacity of CBG for cortisol does not differ in adults with AN compared with controls (12), and elevations have been reported not only in total, but also in free plasma cortisol in adult AN women (20,37). To determine whether an acquired partial glucocorticoid resistance is the cause of hypercortisolemia in AN, investigators have examined expression of glucocorticoid receptors in adults with this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the hyperactivity of the HPA axis differs in depression and AN, with a greater involvement of AVP in depressive disorder and perhaps more reliance on CRH to drive the axis in AN [98] . Some authors proposed malnutrition as the main determinant responsible for HPA axis alterations, because of the significant correlation between pathological DST results and the weight loss already mentioned [114][115][116][117] . Consistent with this interpretation is that the weight recovery is associated with a normalization of plasmatic and urinary cortisol levels [94,97] and with a significant decrease in the number of secretory bursts [97] .…”
Section: The Hpa Axis In the Specific Eating Disordersmentioning
confidence: 99%
“…Studies on anorexia patients also have demonstrated increased plasma cortisol, reflecting both increased production and decreased metabolism of this hormone (Walsh et al, 1981). Although these anomalies normalize after weight restoration (Rolla et al, 1984), they may play a significant role in maintaining the disorder. Underweight anorexics have low levels of CSF leptin (Hebebrand et al, 1997).…”
Section: Pathophysiologymentioning
confidence: 99%